FUNCTIONAL ACTIVITY OF MURINE B CELL: A ROLE OF MICROENVIRONMENT - I. N. Dyakov; I. V. Grigoriev; E. V. Sidorova; I. N. Chernyshova (Медицинская иммунология, 2014)
Abstract. To study influence of microenvironment upon functional activity of B cells, we used experimental models of adoptive cell transfer from CBA to congenic CBA/N mice lacking CD5+ B-1 cells, and cocultivation of CBA/N splenocytes with spleen, or peritoneal CBA cells. B cell activity was determined as numbers of IgM-producing cells, and as amounts of cells producing antibodies to a T-independent antigen type 2 (polyvinylpirrolidone). In vivo distribution of transferred cells was determined as the numbers of cells stained with a vital dye (CDFA-SE) in spleen and peritoneum of recipients. Intravenous injection of CBA splenocytes resulted into a significant (3- to 4-fold) increase in numbers of IgM-producing cells in the spleens of xid–recipients, where their levels reached those of CBA mice. Intravenous injection of CBA/N splenocytes into xid-mice did not induce any increase of IgM-producers in their spleen. That means that increased number of IgM-producers in recipient spleen is due to donor cells, presumably, CD5+ B-1 lymphocytes. Meanwhile, restoration of immune response to polyvinylpirrolidone in xid-mice following transfer of CBA splenocytes was not successful. IgM-producing cells were undetectable in peritoneum of intact mice (both CBA and CBA/N). Intraperitoneal transfer of CBA splenocytes also did not induce their accumulation. It could mean that peritoneal microenvironment inhibits B cell activity. Meanwhile, intravenous injection of «silent» peritoneal cells into CBA/N mice brought about great increase of IgM-producers in recipient spleen, i.e., the «job» of B cells was permitted in other microenvironment. The results yielded in vivo are in agreement with data of in vitro experiments. Addition of CBA splenocytes or peritoneal cells (10-50%) to CBA/N splenocytes induced sharp increase of IgM-producing cells in the cultures. The data obtained provide evidence for a decisive role of microenvironment in functional activity of murine B lymphocytes.